(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This essay analyses the legislation’s shortcomings regarding the burial of aborted fetuses. With the aim of suggesting some revisions of the national legislation in this field, in a context of inaction by the legislator, the paper analyses in particular: a) the question concerning the right to choose the fate of the fetus; b) the possibility of giving the fetus to scientific research, also in consideration of some uses, such as that relating to the experimentation and production of vaccines (also against Covid-19); c) the difficulty of conceiving that the fetus has a right to be buried.